(untitled) (Fiep Bulletin - online, 2011)
This study examined the influence of the Gymnastics program in pain, () the secretaries (them) a college in Viçosa, MG. We used a group of 11 employees, with ages ranging from 21 to 55 years, 9 women and 2 men, secretaries who work for this institution. To collect data we used the questionnaire Topography of Pain. There were two collections of the protocol, one before the implementation of Gymnastics and again after 7 weeks of intervention. From the data collected, there was 100% improvement in complaints of pain in the eye, shoulder, wrist, 75% reduction in the cervical, thoracic region in 80% and 36.37% in the lumbar region. We conclude that the Gymnastics was effective in reducing pain of secretaries, which is a low-cost strategy, which improves the pain conditions and therefore the quality of life, which reduces the rate of absenteeism and increases productivity for the company.